Multiple Means by Which Nitric Oxide can Antagonize Photodynamic Therapy - W. Girotti, Albert; M. Fahey, Jonathan; Korytowski, Witold (Current Medicinal Chemistry, 2016)
Photodynamic therapy (PDT) is a unique site-specific treatment for eradicating a variety of solid tumors, including prostate, lung, bladder, and brain tumors. PDT is a three-component modality involving (i) administration of a photosensitizing agent (PS), (ii) PS photoexcitation by visible or near-infrared light, and (iii) molecular oxygen. Upon photoexcitation, PS gives rise to tumor-damaging reactive oxygen species, most prominently singlet oxygen (1O2). Previous studies revealed that endogenous nitric oxide (NO) in various mouse tumor models significantly reduced PDT effectiveness. Recent studies in the authors’ laboratory indicated that NO produced by photostressed tumor cells per se can elicit anti-PDT effects. For example, breast cancer COH-BR1 and prostate cancer PC3 cells exhibited a rapid and prolonged upregulation of inducible nitric oxide synthase (iNOS) after sensitization with 5- aminolevulinic acid (ALA)-induced protoporphyrin-IX, followed by broad-band visible irradiation. Use of iNOS inhibitors and NO scavengers demonstrated that iNOS/NO played a key role in cell resistance to apoptotic photokilling. Moreover, cells surviving an ALA/light challenge proliferated, migrated, and invaded more rapidly than controls, again in iNOS/NOdependent fashion. Thus, NO was found to play a crucial role in various manifestations of enhanced aggressiveness exhibited by remaining live cells. Recent work has revealed that induced NO in PDT-targeted PC3 cells can also translocate and increase aggressiveness of non-targeted bystander cells. These negative and potentially tumor-promoting side effects of NO in PDT may be averted through use of iNOS inhibitors as adjuvants. Each of the above aspects of PDT antagonism by NO will be discussed in this review.
Keywords: Nitric oxide